Komunitas ikan karang herbivora di perairan Aceh bagian utara - Edi Rudi; Nur Fadli (Depik, 2012)
Abstract. Herbivory reef fish is the most important of fish tropic group in the coral reef ecosystem.Hence, the objective of this study was to provide reliable data and information on herbivory reef fish based on management types in the northern Acehnese reef. Underwater Visual Census Techniques was used to collect the data at 20 sites around Weh Island and Aceh Besar. This study found 32 herbivory reef fishes species from five families in northern Acehnese reef. Densities of herbivory reef fish were varied from 27 to 104 ind./transect,while species numbers were also varied from 6 to 14 species/site. Family Acanthuriidae was the highest in species number, i.e. 19 species. Densities of herbivory reef fish in sites that were protected under the management authority of Sabang Weh Island were not significantly higher compare with sites from open access areas. Keywords: herbivory reef fish, coral reef, visual census technique, Aceh